2016
DOI: 10.1117/12.2233782
|View full text |Cite
|
Sign up to set email alerts
|

Holographic beam mapping of the CHIME pathfinder array

Abstract: The Canadian Hydrogen Intensity Mapping Experiment (CHIME) Pathfinder radio telescope is currently surveying the northern hemisphere between 400 and 800 MHz. By mapping the large scale structure of neutral hydrogen through its redshifted 21 cm line emission between z ∼ 0.8 − 2.5 CHIME will contribute to our understanding of Dark Energy. Bright astrophysical foregrounds must be separated from the neutral hydrogen signal, a task which requires precise characterization of the polarized telescope beams. Using the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Further improvements to the beam model are under active development. In particular, holography observations of both steady sources and pulsars are being used to refine the model of the primary beam (Berger et al 2016).…”
Section: Source Localizationmentioning
confidence: 99%
“…Further improvements to the beam model are under active development. In particular, holography observations of both steady sources and pulsars are being used to refine the model of the primary beam (Berger et al 2016).…”
Section: Source Localizationmentioning
confidence: 99%
“…For example, Neben et al (2016) and Line et al (2018) use the ORBCOMM satellite to map the antenna response. Holography, a well-known technique in radio astronomy, is also used to study the instrument response (Berger et al 2016). Recently, Virone et al (2014), Pupillo et al (2015), Jacobs et al (2017), and de Lera Acedo et al (2018) have demonstrated that we can make direct measurements of the primary beam using unmanned aerial vehicles; however, they are accompanied by challenges that require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…However, extensive radio surveys of the Milky Way galactic center have not found enough pulsars to conclusively strengthen or invalidate the hypothesis that dark matter implodes neutron stars in that region. Fortuitously, the unprecedented sensitivity of laser interferometer gravitational wave detectors at LIGO/Virgo [8], the broad optical purview of DES [9,10], BlackGEM [11], and other optical telescopes, as well as kilo-channel radio reception at CHIME [12] and HIRAX [13], are better scrutinizing the dynamics of neutron stars and black holes. Indeed, recently a neutron star merger was found both in gravitational waves [14] and follow-on telescope observations [15].…”
Section: Introductionmentioning
confidence: 99%